Bagaimana Konseling Karir Teknik Reframing dapat Mengubah Paradigma Adaptasi Karir Mahasiswa? - Fitra Fajar Rostiawan; Wahyu Nanda Eka Saputra (Universitas PGRI Kanjuruhan Malang, 2024)
Millennial and Generation Z students face increasingly complex career adaptation challenges due to the rapidly changing dynamics of the job market, including digitalization and market uncertainty. Low self-confidence and difficulties in managing career transitions are significant barriers in preparing them to enter the workforce. This study aims to explore the effectiveness of reframing techniques in career counseling to enhance the adaptability of Millennial and Generation Z students. Using a literature review method, this study analyzes the challenges of career adaptation and the potential for innovative interventions. The results indicate that students face obstacles such as low self-confidence and difficulties in managing career transitions. Reframing techniques are proposed as an approach to transform career adaptation paradigms through the integration of digital technology and consideration of contextual factors. The study concludes that career counseling using reframing techniques has the potential to comprehensively improve career adaptability, with recommendations for long-term measurement and the development of more integrative intervention models in higher education